Faktor Yang Memengaruhi Tingkat Kelelahan Perawat Di Rumah Sakit Umum Mitra Medika Amplas Tahun 2024 - Santi Asria Lubis; Nur Aini; Yuniati Yuniati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Work fatigue experienced by intensive care room nurses shows several symptoms that are often experienced when nurses are tired, namely drowsiness, difficulty concentrating and physical fatigue. The sleepiness experienced by the nurse was indicated by frequent yawning and wanting to lie down. The aim of this research is to determine the factors that influence the level of work fatigue of nurses at Mitra Medika Amplas General Hospital in 2022. This research is a type of quantitative research with a cross-sectional approach. The population in this study were all nurses at the Mitra Medika Amplas General Hospital in 2022. The sample in this study was 93 people, using purposive sampling, namely taking samples according to the wishes of the researcher. Data was collected using questionnaires and interviews, then processed computerized. Quantitative data analysis was carried out in 3 stages, namely univariate, bivariate and multivariate analysis using Chi-Square, if p ≤ 0.05 then there is an influence between the dependent and independent variables. Statistical test results: age (p value 0.001), gender (p value 0.002), BMI (p value 0.005, education (p value 0.001), sleep patterns (p value 0.001), length of service (p value 0.001), physical work ( p value 0.009), length of work (p value 0.008), it can be concluded that there is a relationship between age, gender, BMI, education, sleep patterns, length of service, length of work, and the level of work fatigue of nurses at Mitra Medika Amplas General Hospital. 2022. The conclusion of this research is that there is a relationship between age, gender, BMI, education, sleep patterns, length of service, length of work, and the level of work fatigue of nurses at Mitra Medika Amplas General Hospital in 2022. It is recommended that Mitra Medika Amplas General Hospital be able to improve health services as well as existing infrastructure in hospitals